Update on Dendritic Cell-Induced Immunological and Clinical Tolerance - Obregon, Carolina; Kumar, Rajesh; Pascual, Manuel Antonio; Vassalli, Giuseppe; Golshayan, Déla (Frontiers in Immunology, 2017)
Dendritic cells (DCs) as highly efficient antigen-presenting cells are at the interface of innate and adaptive immunity. As such, they are key mediators of immunity and antigen-specific immune tolerance. Due to their functional specialization, research efforts have focused on the characterization of DCs subsets involved in the initiation of immunogenic responses and in the maintenance of tissue homeostasis. Tolerogenic DCs (tolDCs)-based therapies have been designed as promising strategies to prevent and control autoimmune diseases as well as allograft rejection after solid organ transplantation (SOT). Despite successful experimental studies and ongoing phase I/II clinical trials using autologous tolDCs in patients with type 1 diabetes, rheumatoid arthritis, multiple sclerosis, and in SOT recipients, additional basic research will be required to determine the optimal DC subset(s) and conditioning regimens to promote the efficacy of tolDCs-based treatments in vivo. In this review, we discuss the characteristics of human DCs and recent advances in their classification, as well as the role of DCs in immune regulation and their susceptibility to in vitro or in vivo manipulation for the development of tolerogenic therapies, with a focus on the potential of tolDCs for the treatment of autoimmune diseases and the prevention of allograft rejection after SOT.